III. AHMED DÖNEMİNDE PARANIN DURUMU - Danık, Sevda (Bahir SELÇUK [EN], 2022)
1699 Karlofça Antlaşması’ndan sonra sosyal ve ekonomik hayatta başlayan gelişmeler III. Ahmed döneminde de devam etmiştir. Bu dönemde Osmanlı Devleti batı tarzında yenilikler yapmaya başlamış; batı ile siyasi, sosyal, kültürel ve ekonomik ilişkiler geliştirilmiş, yeni bir hayat tarzı ortaya çıkmıştır. Yeni köşkler ve kasırlar inşa edilmiş, mimaride Avrupa tesiri görülmeye başlamıştır. Matbaa açılmış, önemli eserler Türkçeye çevrilmiş, tersane ıslah edilmiş, tulumbacı ocağı kurulmuş ve tıp alanında gelişmeler yaşanmıştır. Büyük şehirlerde sanayi imalatı genişlemiş, yeni faaliyet dalları ortaya çıkmış; başta dokuma sanayi olmak üzere, zirai üretim ve ihracat artmıştır. Siyasi, sosyal, kültürel ve ekonomik alandaki bu gelişmelere, paradaki gelişmeleri de eklemek mümkündür. Bu çalışmada III. Ahmed dönemi para yönünden incelenmiş; para konusunda yapılan düzenlemeler ve yaşanan gelişmeler, tedavülde yaygın olarak bulunan paralar, Mısır Darphanesi ve ayarı düşük para darbı, altın ve gümüşün dışarıya kaçırılması, kalpazanlık olayları, paraların rayiçleri ve sikke tashihleri konularına değinilmiştir.

The developments that started in social and economic life after the Treaty of Karlowitz in 1699 continued during the reign of Ahmed III. In this period, the Ottoman Empire started to make innovations in the western style; political, social, cultural and economic relations with the West have been improved and a new lifestyle has emerged. New mansions and pavilions were built, and European influence began to be seen in architecture. A printing house was opened, important works were translated into Turkish, the shipyard was rehabilitated, a fire brigade was established, and there were developments in the field of medicine. Industrial production expanded in big cities, new branches of activity emerged; Agricultural production and exports have increased, especially in the weaving industry. It is possible to add the developments in money to these developments in the political, social, cultural and economic fields. In this study, III. Ahmed period was examined in terms of money; The regulations and developments in money, the common coins in circulation, the Egyptian Mint and the mintage of lightly coins, the smuggling of gold and silver, counterfeiting incidents, the fair values of coins and coin corrections are discussed.
The State of Money During the Reign of Ahmed III